Evaluation of Information Technology Governance Using BAI Domain In Hospital - Fernando, Erick (International Journal of Science, Technology & Management, 2023)
The governance of information technology in hospitals is a crucial component in facilitating the alignment of information technology initiatives with the strategic objectives of XYZ hospital, thereby contributing to the achievement of its organizational goals. XYZ hospital is currently facing a number of challenges, one of which pertains to the Information System utilized for delivering services to visitors. The resolution of this problem can be achieved through the implementation of an assessment using the Cobit 5 framework, specifically targeting the BAI domain. This approach aims to offer recommendations for enhancing the value of capability levels, thereby improving information technology governance within the hospital setting. The results of the investigation conducted on the evaluation of information technology governance utilizing the Cobit 5 framework at "XYZ" hospital demonstrate that the BAI Domain, particularly BAI Domain 05, has attained a maturity level of 3, whereas BAI Domain 08 has attained a maturity level of 2. The two domains in question demonstrate the least developed levels of maturity when compared to the remaining domains. In contrast, BAI Domains 02, 03, 06, 09, and 10 have attained a maturity level of 4, denoting a heightened level of maturity. Finally, BAI Domains 01, 04, and 07 have successfully attained the intended level of maturity.